Improvement in cycling stability of Prussian blue analog-based aqueous sodium-ion batteries by ligand substitution and electrolyte optimization. (20th September 2022) - Pan, Tsung-You; Ruqia,; Wu, Cheng-Yen; Ni, Chung-Sheng; Gull, Sanna; Haider, Ali; Chen, Han-Yi
Abstract: In this study, we investigated the effects of ligand substitution in Prussian blue analog (PBA) cathode materials on the performance of aqueous sodium-ion batteries. NaCu[Fe(CN)6 ] (NaCuHCF) and ligand-modified PBAs, Nax Cu[Fe(CN)5 (C6 H4 N2 )] (Nax CuCNPFe), and Nax Cu[Fe(CN)5 (CH3 C6 H4 NH2 )] (Nax CuTolFe) were tested in different electrolytes. The Nax CuCNPFe and Nax CuTolFe cathodes exhibited the best capacity retention of ∼50% after 2000 cycles in 1 M Na2 SO4, which is much higher than that of the NaCuHCF cathode (0% capacity remained after 2000 cycles). To understand the charge–discharge mechanism of PBA cathodes, in situ synchrotron X-ray absorption spectroscopy and X-ray diffraction were performed. To demonstrate practical energy storage applications, PBAs were tested in full-cell configurations with an anode made of sodium titanium phosphate (NTP) coated with reduced graphene oxide and carbon (NTP@C@RGO). The Nax CuCNPFe//NTP@C@RGO and Nax CuTolFe//NTP@C@RGO full cells in 17 m NaClO4 aqueous electrolyte exhibited high power densities of up to 4338 W kg −1 (with an energy density of 18.11 Wh kg −1 ) and 4742 W kg −1 (with an energy density of 11.87 Wh kg −1 ), respectively. Our study demonstrates the potential of optimizing organic ligands in PBAs and electrolytes for the improvement of the cycling stability of high-power aqueous sodium-ion batteries.